Association of Mid-sagittal Anteroposterior Diameter of Lumbar Canal in Patients with Low Back Pain using MRI: A Cross-sectional Study from West Bengal, India - Chinmay Nandi; Dipankar Bhaumik; Krishnendu Bhowmik; Kaushik Mitra (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Lumbar spinal canal stenosis is the progressive narrowing of spinal canal that causes compression of nerve roots before their exit. The presenting symptoms of spinal canal stenosis includes bilateral lower extremity pain, altered sensation in both legs and poorly localised weakness and generally associated with low back pain. Determination of normal diameter and its variation with development of low back pain could prove useful in determining the aetiology and outcome of congenital or acquired causes of stenosis like spondylolisthesis, Paget’s disease, fluorosis, etc. Aim: To measure and compare the mid-sagittal anteroposterior diameter of lumbar canal in symptomatic cases with low back pain and asymptomatic subjects using Magnetic Resonance Imaging (MRI). Materials and Methods: The present study was a hospital- based cross-sectional, observational study involving Outpatient Department (OPD) patients of Bangur Institute of Neurosciences, Kolkata, West Bengal, India, was undertaken from May 2012 to July 2012. The study participants were selected by systematic random sampling. Total number of 102 cases were investigated in the present study. Out of these, 52 cases were symptomatic patients of low back pain and rest 50 cases were asymptomatic. Magnetic Resonance Imaging (MRI) was done to estimate the mid-sagittal anteroposterior diameter at different levels of lumbar canal. Unpaired t-test was used as test of significance using Statistical Package for the Social Sciences (SPSS) version 19.0. A p-value <0.05 was considered as statistically significant. Results: In the present study, in the asymptomatic group, the anteroposterior diameter at the intervertebral disc level- between L1-L2=18.364±1.4351 mm, L2-L3=17.470±1.3298 mm, L3-L4=16.670±1.6042 mm, L4-L5=15.200±1.8906 mm, L5-S1=14.196±2.1092 mm. Mean diameter of central lumbar vertebral canal was found to be lower in symptomatic cases with low back pain at different vertebral levels and the difference was found to be statistically significant between symptomatic and asymptomatic subjects. It was found that age of presentation did not show any statistical significance with the presence of low back pain. Conclusion: The lumbar vertebral canal diameter was found to be significantly lower in subjects with low back pain than subjects having no complaints.